2016
DOI: 10.1016/j.jhep.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Childhood predictors of adult fatty liver. The Cardiovascular Risk in Young Finns Study

Abstract: The increase in pediatric obesity emphasizes the importance of identification of children and adolescents at high risk of fatty liver in adulthood. We used data from the longitudinal Cardiovascular Risk in Young Finns Study to examine the associations of childhood (3-18years) risk variables with fatty liver assessed in adulthood at the age of 34-49years. The findings suggest that a multifactorial approach with both lifestyle and genetic factors included would improve early identification of children with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 51 publications
1
53
0
2
Order By: Relevance
“…21 Genetic variants may be better predictors in younger individuals and even over longer follow-up periods. We have previously shown for other outcomes, such as adult hypertension, 34 dyslipidemia, 35 fatty liver 36 and type 2 diabetes mellitus, 37 that genetic information provides predictive information in addition to nongenetic childhood risk factors. In this study we confirm similar findings in adulthood obesity prediction.…”
Section: Discussionmentioning
confidence: 99%
“…21 Genetic variants may be better predictors in younger individuals and even over longer follow-up periods. We have previously shown for other outcomes, such as adult hypertension, 34 dyslipidemia, 35 fatty liver 36 and type 2 diabetes mellitus, 37 that genetic information provides predictive information in addition to nongenetic childhood risk factors. In this study we confirm similar findings in adulthood obesity prediction.…”
Section: Discussionmentioning
confidence: 99%
“…In the Cardio vascu lar Risk in Young Finns Study 90 , after a follow up of 31 years, adult NAFLD was predicted by modifiable as well as non modifiable risk factors during childhood, including BMI and plasma insulin levels, male sex, genetic background (that is, PNPLA3 and TM6SF2 variants) and low birth weight, an emerging risk factor for adulthood NAFLD. Overall, these observations mean that NAFLD and its complications, including HCC, are more likely to be antici pated at younger age, yielding a possible reduction of life expectancy and an additional societal burden.…”
Section: Incidence Of Nafld and Future Projections In Europementioning
confidence: 99%
“…In this issue, Suomela et al [11] report the childhood predictors of adult NAFLD, as determined by ultrasonography at follow-up of 31 years, in the Cardiovascular Risk in Young Finns Study (n=2,042), a population-based cohort. The authors had previously shown that the determinants of fatty liver evaluated at adulthood in the same individuals were waist circumference, alanine aminotransferase, body mass index (BMI), male sex, apolipoprotein B, systolic blood pressure, alcohol intake, insulin and low physical activity index [12].…”
mentioning
confidence: 99%